Analysis of affecting factors on patient safety culture in public and private hospitals in Iran - Amir Hossein Khoshakhlagh; Elham Khatooni; Isa Akbarzadeh; Saeid Yazdanirad; Ali Sheidaei (BMC, 2019)
Abstract Background Patient safety culture is one of the main components of the quality of health services and is one of the main priorities of health studies. Accordingly, this study aimed to determine and compare the views of healthcare staff on the patient safety culture and the impact of effective factors on patient safety culture in public and private hospitals in Tehran, Iran. Methods This cross-sectional study was carried out on a sample of 1203 health care workers employed in three public and three private hospitals in Tehran, Iran. Stratified random sampling was used in this study. Data were collected using the Maslach burnout inventory and patient safety culture questionnaire (HSOPSC). IBM SPSS v22 and Amos v23 were used to perform path analysis. Results Eight hundred sixty-seven (72.57%) females and 747 (27.43%) males with a mean age of 33.88 ± 7.66 were included. The average percentage of positive responses to the safety culture questionnaire in public and private hospitals was 65.5 and 58.3%, respectively. The strengths of patient safety culture in public hospitals were in three dimensions including non-punitive response to errors (80%), organizational learning-continuous improvement (79.77%), and overall perceptions of patient safety (75.16%), and in private hospitals, were three dimensions including non-punitive responses to errors (71.41%), organizational learning & continuous improvement (69.24%), and teamwork within units (62.35%). The type of hospital and work-shift hours influenced the burnout and patient safety questionnaire scores (P-value < 0.05). The path analysis results indicate the fitness of the proposed model (RMSEA = 0.024). The results showed a negative impact of a work shift (β = − 0.791), occupational burnout (β = − 0.554) and hospital type (β = − 0.147) on the observance of patient safety culture. Conclusion Providing feedback on errors and requirements for the frequent incident reporting, and patient information exchange seem necessary to promote the patient safety culture. Also, considering the negative impact of the shift work and burnout on patient safety culture, by planning and managing these factors appropriately, correct actions could be designed to improve the safety culture.